Vegetable oil as bio-lubricant and natural additive in lubrication: a review - Masripan, Nor Azmmi; Salim, Mohd Azli; Omar, Ghazali; Mansor, Muhd Ridzuan; Md. Saad, Adzni; Abdul Hamid, Nurfaizey; Mohamad, Imran Syakir; Dai, Feng (Universiti Malaysia Perlis, 2020)
Due to the decreasing petroleum reserves and environmental issues, the approach of using vegetable oil as lubricant has drawn the researchers’ attention. In comparison to mineral-based lubricant, the vegetable based-oil bio-based lubricant has better physical properties, high lubricity, renewable, and biodegradable. The source of bio-based lubricant can be virgin natural oil, or processed fruit waste. This review discusses the vegetable oils as bio-lubricant and natural additive in lubrication according to the current findings. A brief discussion of physicochemical and tribological properties findings completes the review.